Safe Switch to an Oral Two‐Drug Regimen Based on Dolutegravir in People With Vertically Acquired HIV‐1: An Observational Multicenter Study - Giulia Meraviglia; Anna Sala; Francesco Bassani; Laura Labate; Gabriele Pagani; Vania Giacomet; Antonio Di Biagio; Stefano Rusconi (Health Science Reports)
ABSTRACT Background and Aims People with vertically acquired HIV‐1 are exposed to antiretroviral drugs throughout their lives. Two‐drug regimens based on dolutegravir (DTG) are increasingly popular, showing excellent safety and efficacy and giving the opportunity to reduce toxicity and drug burden. However, studies reporting experience in this special population are still lacking. With this study, we evaluated the efficacy and safety of a switch to a two‐drug regimen based on DTG in young people with vertically acquired HIV‐1 infection. Methods This retrospective, multicenter study included subjects with vertically acquired HIV‐1 infection who switched from a combination antiretroviral therapy to a two‐drug regimen with DTG associated with lamivudine, non‐nucleoside reverse transcriptase inhibitors, or boosted protease inhibitors. Results The study included 27 subjects. All of them were virologically suppressed at the moment of the switch except two, with CD4+ lymphocyte T count > 200 cell/mm3. With a median follow‐up of 24.6 months, no virologic failure was detected after the switch except for one patient with poor adherence, and there was no significant difference in CD4+ lymphocyte T count (p = 0.179). Renal function and lipid profile were not influenced by the switch. No side effects have been reported. Conclusion Our experience supports the switch to a two‐drug regimen based on DTG for people with vertically acquired HIV‐1, being safe and effective in maintaining virologic suppression and an adequate CD4+ lymphocyte T count.